Exploring Chinese herbal medicine for ischemic stroke: insights into microglia and signaling pathways - Zhang, Wenjing; Xu, Haoqun; Li, Chong; Han, Bingbing; Zhang, Yimin (Frontiers in Pharmacology, 2024)
Ischemic stroke is a prevalent clinical condition affecting the central nervous system, characterized by a high mortality and disability rate. Its incidence is progressively rising, particularly among younger individuals, posing a significant threat to human well-being. The activation and polarization of microglia, leading to pro-inflammatory and anti-inflammatory responses, are widely recognized as pivotal factors in the pathogenesis of cerebral ischemia and reperfusion injury. Traditional Chinese herbal medicine (TCHMs) boasts a rich historical background, notable efficacy, and minimal adverse effects. It exerts its effects by modulating microglia activation and polarization, suppressing inflammatory responses, and ameliorating nerve injury through the mediation of microglia and various associated pathways (such as NF-κB signaling pathway, Toll-like signaling pathway, Notch signaling pathway, AMPK signaling pathway, MAPK signaling pathway, among others). Consequently, this article focuses on microglia as a therapeutic target, reviewing relevant pathway of literature on TCHMs to mitigate neuroinflammation and mediate IS injury, while also exploring research on drug delivery of TCHMs. The ultimate goal is to provide new insights that can contribute to the clinical management of IS using TCHMs.